Kardiochirurgia dorosłychTricuspid valve replacement in a re-operated patient with severe tricuspid regurgitation and constrictve pericarditis - Woźniak, Sebastian; Kołsut, Piotr; Hoffman, Piotr; Kordybach, Maria; Michałowska, Ilona; Różański, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Presentation of a clinical case of a 50-year-old female patient admitted emergently to the Second Clinic of Cardiac Surgery and Trans-plantology due to decompensated right heart failure caused by significant tricuspid insufficiency and constrictive pericarditis. The tricuspid ring diameter and the degree of valve insufficiency were assessed on the beating heart, with extracorpo- real circulation. Because of the size of the ring (27 mm) and the patient’s body surface, requiring a 31-mm prosthesis, extra-anatomic implantation of a biological valve prosthesis epic SJM 31 was carried out, leaving the coronary sinus ostium on the side of the right chamber – Barnard-Schrire’s procedure. The implantation of a biological valve seems an optimal solution for the discussed case. A repair surgery and the uncertainty of its outcome in this patient with concomitant diseases have carried too big a risk.